2019
DOI: 10.1080/14763141.2019.1675751
|View full text |Cite
|
Sign up to set email alerts
|

Variability of lumbar spinal alignment among power- and weightlifters during the deadlift and barbell back squat

Abstract: The aims of the study were to evaluate the relative and absolute variability of upper (T11-L2) and lower (L2-S2) lumbar spinal alignment in power-and weightlifters during the deadlift and back squat exercises, and to compare this alignment between the two lifting groups. Twenty-four competitive powerlifters (n = 14) and weightlifters (n = 10) performed three repetitions of the deadlift and the back squat exercises using a load equivalent to 70% of their respective one-repetition maximum. The main outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Exercises performed by the strength-trained participants in the present study are used in powerlifting competitions and are commonly performed by experienced resistance trainers to maximise muscle adaptations [ 35 ]. Additionally, the squat and deadlift require high axial loading as well as increased lumbar spine stability compared to traditional resistance exercises (e.g., machine knee extension and flexion) [ 36 ]. As such, it seemed plausible that targeting participants well trained in the bench press, squat, and deadlift would provide a cohort that has strong “core” musculature, which, as mentioned previously, consists of the respiratory muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Exercises performed by the strength-trained participants in the present study are used in powerlifting competitions and are commonly performed by experienced resistance trainers to maximise muscle adaptations [ 35 ]. Additionally, the squat and deadlift require high axial loading as well as increased lumbar spine stability compared to traditional resistance exercises (e.g., machine knee extension and flexion) [ 36 ]. As such, it seemed plausible that targeting participants well trained in the bench press, squat, and deadlift would provide a cohort that has strong “core” musculature, which, as mentioned previously, consists of the respiratory muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Although, it was also observed that IC was diminished following the high-volume session compared to the control session which provides evidence that inspiratory muscle function was acutely impaired. The main inspiratory muscle is the diaphragm (Enright et al, 2006), and this muscle together with other respiratory muscles assists with stabilisation of the trunk during exercises with high axial loading such as deadlifts and squats (Aasa et al, 2019). The high-volume session most likely required slightly greater work to be accomplished by the inspiratory muscles from the perspective of ensuring adequate trunk stabilisation, thus leading to inspiratory muscle fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Both practices are similar to squatting. In weightlifting, the squat is performed by putting a weight bar over the upper back and shoulder, flexing hips/knees until thighs are parallel to the floor, and then pressing weight back to the initial vertical position [ 12 , 13 ]. A very similar position to be performed by the costalero each time they lift up the throne.…”
Section: Introductionmentioning
confidence: 99%